2010
DOI: 10.1093/brain/awq013
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated variants of Lesch-Nyhan disease

Abstract: Lesch–Nyhan disease is a neurogenetic disorder caused by deficiency of the enzyme hypoxanthine–guanine phosphoribosyltransferase. The classic form of the disease is described by a characteristic syndrome that includes overproduction of uric acid, severe generalized dystonia, cognitive disability and self-injurious behaviour. In addition to the classic disease, variant forms of the disease occur wherein some clinical features are absent or unusually mild. The current studies provide the results of a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 71 publications
2
120
0
3
Order By: Relevance
“…3 The condition is almost exclusively diagnosed in the paediatric population though new diagnosis has been documented in adults. 20 Benz CMK et al 21 described the self-destructive behaviour of patients with LNS usually starts between the ages of 1.5 to 2 years or shortly after the primary teeth eruption. The auto-aggressive behaviour is manifested as lips and tongue biting, scratching with the fingernails, head banging.…”
Section: Discussionmentioning
confidence: 99%
“…3 The condition is almost exclusively diagnosed in the paediatric population though new diagnosis has been documented in adults. 20 Benz CMK et al 21 described the self-destructive behaviour of patients with LNS usually starts between the ages of 1.5 to 2 years or shortly after the primary teeth eruption. The auto-aggressive behaviour is manifested as lips and tongue biting, scratching with the fingernails, head banging.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, patients with attenuated phenotypes are designated Lesch-Nyhan variants (LNV) 4 . The mildest form of LNV includes only overproduction of uric acid and its associated problems.…”
Section: To the Editormentioning
confidence: 99%
“…The Journal of on May 12, 2018 -Published by www.jrheum.org Downloaded from Letter nephrolithiasis 4,5,6 . The gout resulting from HPRT deficiency is remarkable in its severity and its propensity to form tophi 5,6 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Patients develop nephrolithiasis, gouty arthritis, and neurological manifestations including dystonia, choreoathetosis, ballismus, and a behavioral disease that includes disinhibited behavior and severe, stereotyped self-injury. Epilepsy may occur in LND, with estimates ranging from 2-3% Jinnah et al 2010); however, other studies have found a risk of seizure up to 30%, although this may be due to misinterpretation of abnormal movements as seizure (de Gemmis et al 2010;Markowski-Leeman and Jinnah 2013). Seizures in LND usually begin in childhood, and are typically classified as generalized tonic-clonic .…”
Section: Introductionmentioning
confidence: 99%